Management of Fetal Maceration in a Cross Bred Jersey Cow - A Case Report - P Ramesh,; G S Haritha,; B Srilatha,; K Prabhakar Rao, (The Indian Veterinary Journal, 2024)
A sixth month pregnant Cross bred Jersey cow under second lactation was referred to the Veterinary Clinical Complex, Garividi with the history of straining, mild blood tinged purulent vaginal discharges since 15 days. Upon detailed clinical examination of affected animal, noticed all the vital parameters were within normal range. Per rectal examination revealed firm and thick walled uterus with crepitating fetal mass and relative reduction in size of the uterus. On pervaginal examination, two finger cervical dilatation and foul smelling mucopurulent discharges from the vagina were noticed on day of presentation. Pregnancy was confirmed by using trans rectal ultrasonography revealing scanty fluid in contracted uterus and fragments of fetal skeleton. Initially parturition was induced with parenteral administration of Inj. PGF2α, dexamethasone and calcium borogluconate. After 48 hours of induction noticed expulsion of mucopurulent discharges from vagina with partial dilatation of cervix. Macerated bony fetal parts were removed manually under the guidance of transrectal ultrasonography.